2019
DOI: 10.1182/blood.2018893099
|View full text |Cite
|
Sign up to set email alerts
|

Lobe specificity of iron binding to transferrin modulates murine erythropoiesis and iron homeostasis

Abstract: In this Plenary Paper, the investigators demonstrate that the two monoferric forms of transferrin, the major plasma glycoprotein involved in cellular iron delivery, have functionally distinct effects on erythropoiesis and systemic iron regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Parrow et al recently reported that mice carrying mutations in Trf that prevent iron binding at either lobe have hepatocellular iron overload and decreased liver expression of the iron regulatory hormone hepcidin. 3 These findings provide further support that Trf plays a key role in iron homeostasis and erythropoiesis.…”
Section: Introductionsupporting
confidence: 53%
“…Parrow et al recently reported that mice carrying mutations in Trf that prevent iron binding at either lobe have hepatocellular iron overload and decreased liver expression of the iron regulatory hormone hepcidin. 3 These findings provide further support that Trf plays a key role in iron homeostasis and erythropoiesis.…”
Section: Introductionsupporting
confidence: 53%
“…Both receptors present little to no affinity for Apo-Tf at pH 7.4. Partially saturated transferrin can be found in the circulation [ 32 ], ferric ions binding first to the C-terminal lobe of Tf [ 33 ]. Rabbit TFR1 can bind partially saturated transferrin although its affinity for C-lobe saturated transferrin and N-lobe saturated transferrin is only five times and six times greater than for Apo-Tf [ 34 ].…”
Section: Regulation Of the Transferrin Receptors In Erythroid Cellmentioning
confidence: 99%
“…Aside from its own signaling, TFR2 may also affect EPOR signaling in erythroid cells by regulating EPOR cell surface expression [ 32 , 55 ]. Forejtnikovà et al demonstrated that TFR2 and EPOR associate in the endoplasmic reticulum of erythroblasts and that TFR2 then facilitates the transport of EPOR to cell surface.…”
Section: Signaling Of the Transferrin Receptors And Erythropoiesismentioning
confidence: 99%
“…166,167 Interestingly, not only the diferric form of transferrin has distinct signaling properties than the apotransferrin, but also two monomeric variants elicit differential effects. 168 Two mouse models with genetic disruption of iron binding to either N or C lobe are characterized with high serum NTBI levels, liver iron overload, and deficient hepcidin levels relative to liver iron status, with the last two parameters being more severely affected in mice with the N lobe blockage. The same model was also hallmarked by lower responsiveness to EPO, suggesting that N lobe occupancy has dominant roles in the regulation of erythropoiesis, likely through TFR2, the erythroid regulator of EPO-EPOR signaling.…”
Section: Iron-bound Transferrin As a Signaling Molecule Between Thementioning
confidence: 99%